Preparation method of gold ion layered adsorbent
By combining organic matter with two-dimensional layered materials to form a layered porous structure, the problems of low gold ion recovery efficiency and environmental pollution in the prior art are solved, and efficient and selective gold ion adsorption and recovery are achieved.
Patent Information
- Application Number
- CN202411641250.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has problems of low adsorption efficiency and environmental pollution in the gold ion recovery process, especially the high toxicity of the cyanation method poses a serious threat to the environment.
By using amino groups and hydroxyl groups on organic matter as active sites, it is combined with a two-dimensional layered material to form a layered porous structure, which improves the mechanical strength and specific surface area of the material, thereby achieving efficient selective adsorption of gold ions.
It realizes efficient selective adsorption of gold ions, with large adsorption capacity and high selectivity, and is suitable for the recovery of gold ions in complex component solutions, and the preparation method is simple and the conditions are mild.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gold ion adsorption in solution and relates to a method for preparing a gold ion layered adsorbent. Background Art
[0003] The most widely used gold leaching method at present is the cyanidation method in hydrometallurgy, which is widely used because of its simple process and low cost. However, the high toxicity of cyanide may cause serious pollution to the environment. To this end, a variety of non-cyanidation alternative methods have been developed, such as thiosulfate method, bromination method, iodination method and thiourea method. These methods will dissolve the gangue minerals in the ore into the leachate during the leaching process, forming a complex ion system that coexists with gold ions. The main methods for recovering gold from the leachate are extraction method, displacement method and adsorption method. In contrast, the adsorption method is more suitable for separating gold ions from solutions with low gold concentration and complex systems. Activated carbon, as a widely used adsorbent, is favored because of its simple operation and large specific surface area, but it is easy to adsorb impurities, resulting in reduced adsorption efficiency.
[0004] Therefore, it is necessary to develop a new adsorbent material with specific selectivity for gold ions and large adsorption capacity to improve the gold recovery rate. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a gold ion layered adsorbent. In the present invention, amino groups and hydroxyl groups on organic substances are used as active sites, which are compounded with two-dimensional layered materials through electrostatic effects and chemical crosslinking to form a complex layered porous structure, thereby improving the mechanical strength and specific surface area of the material, thereby achieving efficient and selective adsorption of gold ions. The preparation method is simple, the conditions are mild, the obtained material has a large adsorption capacity and high selectivity, and can be used to recover gold ions in complex component solutions.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a gold ion layered adsorbent, the preparation method comprising:
[0008] (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution;
[0009] (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution;
[0010] (3) mixing the pretreatment solution described in step (1) and the basic solution described in step (2), stirring and adding a cross-linking agent into the emulsion to obtain a reaction material;
[0011] (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain the gold ion layered adsorbent;
[0012] There is no particular order in which steps (1) and (2) are performed.
[0013] In the present invention, amino groups and hydroxyl groups on organic substances are used as active sites, which are compounded with two-dimensional layered materials through electrostatic effects and chemical crosslinking to form a complex layered porous structure, thereby improving the mechanical strength and specific surface area of the material, thereby achieving efficient and selective adsorption of gold ions. The preparation method is simple, the conditions are mild, the obtained material has a large adsorption capacity and high selectivity, and can be used to recover gold ions in complex component solutions.
[0014] It should be noted that layered materials have a two-dimensional structure, and the layers are bonded by van der Waals forces or hydrogen bonds. This structure provides the material with a large specific surface area, thereby increasing the possibility of contact with the target ions and adsorption. The surface of layered materials contains abundant active functional groups, such as hydroxyl, carboxyl and halogenated groups. During the adsorption process, these functional groups can effectively adsorb Au in the solution through the synergistic effect of electrostatic attraction and coordination reaction. 3+ Under acidic conditions, Au in solution 3+ Under the action of electrostatic attraction, the gold ions are guided to the vicinity of the negatively charged functional groups on the surface of the material. Subsequently, the gold ions and the lone pair electrons in the functional groups overlap and transfer electrons to form a stable coordination bond. In addition, due to the catalytic properties of the layered material, the gold ions can be reduced to elemental gold and finally firmly adsorbed on the surface of the material.
[0015] Therefore, the chitosan is compounded with the layered material, which not only solves the problem of small specific surface area and instability of chitosan under acidic conditions, but also significantly improves the adsorption effect of the material on gold ions through the high specific surface area and rich surface functional groups of the layered material. The present invention provides a more promising solution for efficiently recovering gold ions in solution.
[0016] However, the bonding force between the layers of the layered material may be weakened under acidic conditions, thereby causing peeling or disintegration, because water molecules and hydrogen ions penetrate into the layered material, resulting in a certain change in the interlayer distance. To improve the stability of the layered material in an acidic environment, surface functionalization modification and interlayer intercalation modification are generally used to optimize the layered material, but the specific surface area of the material is often reduced during the optimization process, affecting the adsorption capacity, and the preparation process of the material is more complicated and expensive. To solve this problem, layered materials can be composited with other materials. As in the present application, two-dimensional materials and organic materials are hybridized and composited, on the one hand, by forming a stable chemical bond between the two-dimensional material and the organic material, the active sites on the surface of the layered material for gold ion bonding are increased, and the adsorption capacity of the adsorbent is improved. On the other hand, by hybridizing the two-dimensional material and the organic material, the adsorbent material has good rigidity, and the stability of the composite material in a complex environment is improved, so that the adsorbent material can be recycled.
[0017] As a preferred technical solution of the present invention, in step (1), the treating agent includes tetramethylammonium hydroxide or CTAB solution.
[0018] Preferably, the amount of the treating agent is 10mL to 100mL, for example, it can be 10mL, 20mL, 30mL, 40mL, 50mL, 60mL, 70mL, 80mL, 90mL, 100mL, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the ratio of the added amount of the treating agent to the added amount of the two-dimensional material is 1mL:1g~10g, for example, it can be 1mL:1g, 1mL:2g, 1mL:3g, 1mL:4g, 1mL:5g, 1mL:6g, 1mL:7g, 1mL:8g, 1mL:9g, 1mL:10g, etc., but it is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0020] The ratio of the amount of treatment agent added to the amount of two-dimensional material added in the present invention is 1mL:1g~10g, because within this range, the uniform dispersion and surface modification of the two-dimensional material can be effectively ensured; if it is not within this range, such as insufficient amount of treatment agent, it is difficult to achieve sufficient dispersion and modification of the two-dimensional material, thereby affecting the adsorption performance. On the contrary, if too much treatment agent is added, it may cause excessive aggregation or precipitation of the treatment agent itself, affecting the uniformity and stability of the material, and further affecting the overall performance of the composite material.
[0021] As a preferred technical solution of the present invention, in step (1), the two-dimensional material includes any one of Ti3C2Tx, Ti2C, Nb2C or V2C, and is further preferably Ti3C2Tx.
[0022] The two-dimensional material in the present invention refers to a material in which electrons can only move freely (planar motion) on a non-nanoscale (1nm to 100nm) in two dimensions, wherein Ti3C2Tx, a two-dimensional (2D) nanosheet material from the MXene family, is further selected to enable the material to have better conductivity and stronger surface reactivity within the plane.
[0023] It should be noted that Ti3C2Tx in the present invention is a well-known two-dimensional layered material, mainly composed of Ti, C, O and F elements, and is formed by selectively etching aluminum atoms in the ternary carbide Ti3AlC2 sheet.
[0024] As a preferred technical solution of the present invention, the pretreatment time is 12h to 48h, for example, it can be 12h, 14h, 16h, 18h, 20h, 25h, 28h, 30h, 33h, 36h, 38h, 40h, 43h, 45h, 46h, 48h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] The pretreatment time in the present invention is 12h to 48h because within this range the two-dimensional material and the treatment agent can fully react to achieve surface modification and uniform dispersion; if it is not within this range, the treatment time is too short and the material surface may not be fully modified, and the ideal performance cannot be achieved; and too long a treatment time may cause an overreaction, resulting in the destruction or agglomeration of the material structure, thereby affecting the performance and stability of the composite material.
[0026] Preferably, the treatment temperature of the pretreatment is 25°C to 80°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] As a preferred technical solution of the present invention, in step (2), the organic substance includes any one of chitosan, chitosan modified materials or cyclodextrin polymers, and is more preferably chitosan modified materials.
[0028] Preferably, the added amount of the organic substance is 0.1g to 10g, for example, it can be 0.1g, 0.5g, 1g, 2g, 3g, 4g, 5g, 6g, 7g, 8g, 9g, 10g, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] The addition amount of the organic substance in the present invention is 0.1g to 10g, because within this range, it can ensure sufficient reaction and compounding between the organic substance and the two-dimensional material, so that the structure and performance of the adsorbent are improved, and its adsorption capacity and stability are enhanced; if it is not within this range, too low an addition amount may lead to insufficient functionalization of the material and failure to achieve the expected performance; and too high an addition amount may cause excessive modification of the material surface, affect its surface activity, and even cause material agglomeration, thereby reducing the performance of the composite material.
[0030] Preferably, the mass concentration of the acetic acid solution is 1% to 15%, for example, it can be 1%, 3%, 5%, 7%, 9%, 10%, 12%, 14%, 15%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] The reason why the present invention selects acetic acid solution is that organic matter has a high solubility in acetic acid solution, which can effectively dissolve organic matter and provide a suitable acidic environment, which is helpful to improve the reaction activity of organic matter and promote the modification of materials; wherein, the mass concentration of acetic acid solution is 1% to 15%, because within this range, the acetic acid solution can be guaranteed to have sufficient dissolving capacity, and at the same time, the material structure will not be damaged due to too high concentration. If the concentration is too low, the organic matter may not be completely dissolved, affecting the reaction efficiency; and if the concentration is too high, the solution acidity may be too high, affecting the stability of the material structure and the composite effect.
[0032] Preferably, in step (2), the stirring time is 3 h to 12 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] As a preferred technical solution of the present invention, in step (3), the volume ratio of the pretreatment solution to the basic solution is 1:(0.2-5), for example, it can be 1:0.2, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] The volume ratio of the pretreatment solution to the basic solution of the present invention is 1:(0.2-5) because within this range the reaction amount between the two-dimensional material and the organic substance is maintained in the optimal range, and the two can fully react to form a stable complex and a cross-linked structure; if it is not within this range, it may cause incomplete or excessive reaction between the two-dimensional material and the organic substance, thereby affecting the quality and performance of the final product, and even causing instability in the reaction process or the generation of by-products.
[0035] Preferably, the emulsion comprises a mixture of liquid paraffin and Span-80.
[0036] It should be noted that the present invention does not specifically limit the existence form and related ratio of liquid paraffin and Span-80, and those skilled in the art can make adaptive adjustments according to actual conditions, wherein the usage ratio of liquid paraffin to Span-80 can be 35:1; the use of an emulsion dispersion method is conducive to improving the dispersion effect of the sample, ensuring that the components in the emulsion are evenly distributed, thereby forming uniform and fine particles, optimizing the reaction process, and improving the quality and stability of the final product.
[0037] Preferably, the amount of the emulsion is 50 mL to 300 mL, for example, 50 mL, 80 mL, 10 mL, 150 mL, 180 mL, 200 mL, 220 mL, 250 mL, 280 mL, 300 mL, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] The dosage of the emulsion of the present invention is 50mL to 300mL because within this range the emulsion can evenly cover and disperse all reactants, ensuring the uniformity and stability of the reaction; if it is not within this range, the emulsion may be too little and the reactants cannot be fully dispersed, or the emulsion may be too much, resulting in excessive dilution of the reaction system and affecting the reaction efficiency.
[0039] As a preferred technical solution of the present invention, in step (3), the stirring speed is 200 r / min to 800 r / min, for example, it can be 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, in step (3), the stirring temperature is 20°C to 90°C, for example, it can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, in step (3), the stirring time is 2 h to 12 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] As a preferred technical solution of the present invention, in step (3), the cross-linking agent includes any one of diisocyanate, acylated polyethylene glycol, adipic acid chloride, citric acid, ethylene glycol glycidyl ether, glutaraldehyde, polyacrylic acid, tetrafluoroterephthalonitrile, sebacic acid chloride or succinic anhydride, or a combination of at least two thereof, and is further preferably any one of diisocyanate, acylated polyethylene glycol or glutaraldehyde.
[0043] In the present invention, the cross-linking agent further selects any one of diisocyanate, acylated polyethylene glycol or glutaraldehyde because it has better cross-linking efficiency and chemical stability than other materials, can effectively promote the cross-linking reaction between two-dimensional materials and organic substances, improve the structural stability and mechanical properties of the materials, and is suitable for the specific application of the present invention.
[0044] Preferably, the ratio of the amount of the organic substance to the amount of the added cross-linking agent is 1:(1-10), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] The ratio of the amount of organic substance used in the present invention to the amount of cross-linking agent added is 1:(1-10) because within this range, the reaction amount of the cross-linking agent matches that of the organic substance and can react fully, thereby obtaining the best cross-linking effect and material performance; if it is not within this range, it may lead to incomplete cross-linking reaction or excessive cross-linking, resulting in side reactions, thereby affecting the performance and chemical stability of the final material.
[0046] As a preferred technical solution of the present invention, in step (4), the temperature of the washing treatment is 25°C to 40°C, for example, it can be 25°C, 27°C, 29°C, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the washing treatment time is 30 min to 60 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] It should be noted that, in the washing treatment of the present invention, the mixture can be first poured into a filtering device to separate the solid particles from the emulsion mixture through filter paper or a filter membrane, and then initially filtered; the solid particles are rinsed in sequence with petroleum ether, ethanol and deionized water to remove the residual emulsion components; the rinsed solid is placed in an ultrasonic cleaner, and petroleum ether is added again for ultrasonic cleaning to further remove the emulsion attached to the surface.
[0049] Preferably, the drying process is vacuum drying.
[0050] Preferably, the drying temperature is 50°C to 80°C, for example, it can be 50°C, 55°C, 58°C, 60°C, 65°C, 70°C, 75°C, 78°C, 80°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the drying time is 6 h to 12 h, for example, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] The drying time of the present invention is 6h to 12h because the water in the sample can be completely removed within this range; if it is not within this range, it may lead to incomplete drying, leaving too much water inside the material, affecting the adsorption performance of the material, or excessive drying, causing changes or damage to the properties and structure of the material. It should be noted that the drying treatment in the present invention can be to first use a freeze dryer to quickly cool the gold ion layered adsorbent to a relatively low temperature so that the water therein is frozen into solid ice; the sample is placed under vacuum conditions, and the temperature is gradually increased so that the ice is directly sublimated from the solid state to water vapor to avoid the generation of liquid water, thereby achieving the drying process of the sample.
[0053] As a preferred technical solution of the present invention, the preparation method specifically comprises:
[0054] (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution;
[0055] (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution;
[0056] (3) mixing the pretreatment solution described in step (1) and the basic solution described in step (2), stirring and adding a cross-linking agent into the emulsion to obtain a reaction material;
[0057] (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain the gold ion layered adsorbent;
[0058] There is no particular order in which steps (1) and (2) are performed.
[0059] in:
[0060] In step (1), the treating agent includes tetramethylammonium hydroxide or CTAB solution, the amount of the treating agent used is 10mL~100mL, the ratio of the added amount of the treating agent to the added amount of the two-dimensional material is 1mL:1g~10g, the two-dimensional material includes any one of Ti3C2Tx, Ti2C, Nb2C or V2C, the treatment time of the pretreatment is 12h~48h, and the treatment temperature of the pretreatment is 25℃~80℃.
[0061] In step (2), the organic substance includes any one of chitosan, chitosan modified material or cyclodextrin polymer, the added amount of the organic substance is 0.1g to 10g, the mass concentration of the acetic acid solution is 1% to 15%, and the stirring time is 3h to 12h.
[0062] In step (3), the volume ratio of the pretreatment solution to the basic solution is 1:(0.2-5), the emulsion comprises a mixture of liquid paraffin and Span-80, the amount of the emulsion is 50 mL-300 mL, the stirring speed is 200 r / min-800 r / min, the stirring temperature is 20° C.-90° C., the stirring time is 2 h-12 h, the cross-linking agent comprises any one of diisocyanate, acylated polyethylene glycol, adipic acid chloride, citric acid, ethylene glycol glycidyl ether, glutaraldehyde, polyacrylic acid, tetrafluoroterephthalonitrile, sebacic acid chloride or succinic anhydride, and the ratio of the amount of the organic substance to the amount of the cross-linking agent added is 1:(1-10).
[0063] In step (4), the washing treatment temperature is 25°C to 40°C, the washing treatment time is 30min to 60min, the drying treatment is vacuum drying, the drying treatment temperature is 50°C to 80°C, and the drying treatment time is 6h to 12h.
[0064] It should be noted that the gold ion layered adsorbent in the present invention is a layered porous gold ion adsorbent material hybridized with a two-dimensional material and a chitosan-based polymer.
[0065] Exemplarily, the separation and application method of the gold ion layered adsorbent in the present invention may include:
[0066] The gold-containing material (gold ore or circuit board) is leached to obtain a gold-containing leaching solution, in which the gold ions are in the form of [AuCl4] - 、Au(CN) 2- or Au(S2O3)2 3- Form exists;
[0067] The pH value of the leaching solution is adjusted to 1-11, and the leaching solution is passed through an adsorption column filled with 0.01 g / L-10 g / L of a gold ion layered adsorbent to adsorb and recover the gold ions.
[0068] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] In the present invention, amino groups and hydroxyl groups on organic substances are used as active sites, which are compounded with two-dimensional layered materials through electrostatic effects and chemical crosslinking to form a complex layered porous structure, thereby improving the mechanical strength and specific surface area of the material, thereby achieving efficient and selective adsorption of gold ions. The preparation method is simple, the conditions are mild, the obtained material has a large adsorption capacity and high selectivity, and can be used to recover gold ions in complex component solutions. DETAILED DESCRIPTION
[0071] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0072] Example 1
[0073] This embodiment provides a method for preparing a gold ion layered adsorbent, comprising:
[0074] (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution;
[0075] (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution;
[0076] (3) mixing the pretreatment solution of step (1) and the base solution of step (2), stirring and adding a crosslinking agent into the emulsion to obtain a reaction material;
[0077] (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain a gold ion layered adsorbent;
[0078] There is no particular order in which steps (1) and (2) are performed.
[0079] in:
[0080] In step (1), the treatment agent is tetramethylammonium hydroxide solution, the amount of the treatment agent is 10 mL, the two-dimensional material is Ti3C2Tx, the amount of the two-dimensional material added is 10 g, the pretreatment time is 12 h, and the pretreatment temperature is 40°C.
[0081] In step (2), the organic substance is chitosan powder, the amount of the organic substance added is 1 g, the mass concentration of the acetic acid solution is 1%, and the stirring time is 4 h.
[0082] In step (3), the volume ratio of the pretreatment solution to the base solution is 1:0.5, the emulsion includes a mixture of liquid paraffin and Span-80, the amount of the emulsion is 50 mL, the stirring speed is 200 r / min, the stirring temperature is 30° C., the stirring time is 3 h, the cross-linking agent is diisocyanate, and the ratio of the amount of organic substance to the amount of cross-linking agent added is 1:1.
[0083] In step (4), the washing treatment temperature is 25° C., the washing treatment time is 60 min, the drying treatment is vacuum drying, the drying treatment temperature is 50° C., and the drying treatment time is 12 h.
[0084] The chitosan powder of the present invention has a deacetylation degree of ≥95% and a viscosity of 100 mpa.s to 200 mpa.s; Ti3C2 T Specifically, x can be a Ti3C2MXene material whose surface is modified with functional groups such as fluorine (-F), hydroxyl (-OH), and oxygen (-O).
[0085] In this embodiment, tetramethylammonium hydroxide is in the form of a solution, and its concentration is a 25% aqueous solution, which is an analytical grade AR grade.
[0086] Example 2
[0087] This embodiment provides a method for preparing a gold ion layered adsorbent, comprising:
[0088] (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution;
[0089] (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution;
[0090] (3) mixing the pretreatment solution of step (1) and the base solution of step (2), stirring and adding a crosslinking agent into the emulsion to obtain a reaction material;
[0091] (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain a gold ion layered adsorbent;
[0092] There is no particular order in which steps (1) and (2) are performed.
[0093] in:
[0094] In step (1), the treating agent is CTAB solution, the amount of the treating agent is 20 mL, the two-dimensional material is Ti2C, the amount of the two-dimensional material added is 3 g, the pretreatment time is 20 h, and the pretreatment temperature is 50°C.
[0095] In step (2), the organic substance is a chitosan modified material, the amount of the organic substance added is 5 g, the mass concentration of the acetic acid solution is 7%, and the stirring time is 8 h.
[0096] In this embodiment, the chitosan modified material can be a chitosan material modified by cross-linking, grafting or composite methods; it can contain functional groups such as amino (-NH2), hydroxyl (-OH), carboxyl (-COOH), carbamate (-NHCOO-) or amide (-CONH2), sulfhydryl (-SH), sulfate (-SO3H), thioester (-SR) and the like.
[0097] In step (3), the volume ratio of the pretreatment solution to the base solution is 1:3, the emulsion includes a mixture of liquid paraffin and Span-80, the amount of the emulsion is 150 mL, the stirring speed is 400 r / min, the stirring temperature is 50° C., the stirring time is 2 h, the cross-linking agent is glutaraldehyde, and the ratio of the amount of organic substance to the amount of cross-linking agent added is 1:3.
[0098] In step (4), the washing treatment temperature is 30° C., the washing treatment time is 40 min, the drying treatment is vacuum drying, the drying treatment temperature is 60° C., and the drying treatment time is 8 h.
[0099] In this embodiment, the CTAB solution refers to hexadecyltrimethylammonium bromide, and its concentration is 99% aqueous solution.
[0100] Example 3
[0101] This embodiment provides a method for preparing a gold ion layered adsorbent, comprising:
[0102] (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution;
[0103] (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution;
[0104] (3) mixing the pretreatment solution of step (1) and the base solution of step (2), stirring and adding a crosslinking agent into the emulsion to obtain a reaction material;
[0105] (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain a gold ion layered adsorbent;
[0106] There is no particular order in which steps (1) and (2) are performed.
[0107] in:
[0108] In step (1), the treatment agent is tetramethylammonium hydroxide solution, the amount of the treatment agent is 100 mL, the two-dimensional material is Nb2C, the amount of the two-dimensional material added is 10 g, the pretreatment time is 48 h, and the pretreatment temperature is 80°C.
[0109] In step (2), the organic substance is a cyclodextrin polymer, the amount of the organic substance added is 10 g, the mass concentration of the acetic acid solution is 15%, and the stirring time is 8 h.
[0110] In step (3), the volume ratio of the pretreatment solution to the base solution is 1:5, the emulsion includes a mixture of liquid paraffin and Span-80, the amount of the emulsion is 5300 mL, the stirring speed is 800 r / min, the stirring temperature is 60° C., the stirring time is 7 h, the cross-linking agent is polyacrylic acid, and the ratio of the amount of organic substance to the amount of cross-linking agent added is 1:8.
[0111] In step (4), the washing treatment temperature is 40° C., the washing treatment time is 30 min, the drying treatment is vacuum drying, the drying treatment temperature is 80° C., and the drying treatment time is 6 h.
[0112] In this embodiment, the cyclodextrin polymer may be β-cyclodextrin, the purity of which is ≥98%, and the inner diameter of the cavities is 0.7 nm to 0.8 nm.
[0113] Example 4
[0114] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the ratio of the added amount of the treating agent to the added amount of the two-dimensional material is 1 mL:0.8 g, and the other parameters and experimental conditions are the same as those in Example 1.
[0115] Example 5
[0116] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the ratio of the added amount of the treating agent to the added amount of the two-dimensional material is 1 mL:15 g, and the other parameters and experimental conditions are the same as those in Example 1.
[0117] Example 6
[0118] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the amount of organic matter added is 0.08 g, and other parameters and experimental conditions are the same as those in Example 1.
[0119] Example 7
[0120] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the amount of organic matter added is 12 g, and other parameters and experimental conditions are the same as those in Example 1.
[0121] Example 8
[0122] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the mass concentration of the acetic acid solution is 0.9%, and the other parameters and experimental conditions are the same as those in Example 1.
[0123] Example 9
[0124] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the mass concentration of the acetic acid solution is 16%, and the other parameters and experimental conditions are the same as those in Example 1.
[0125] Example 10
[0126] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the volume ratio of the pretreatment solution to the base solution is 1:0.1, and other parameters and experimental conditions are the same as those in Example 1.
[0127] Embodiment 11
[0128] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the volume ratio of the pretreatment solution to the base solution is 1:6, and other parameters and experimental conditions are the same as those in Example 1.
[0129] Example 12
[0130] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the ratio of the amount of organic substance used to the amount of cross-linking agent added is 1:0.8, and other parameters and experimental conditions are the same as those in Example 1.
[0131] Example 13
[0132] This embodiment provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that the ratio of the amount of organic substance used to the amount of cross-linking agent added is 1:11, and other parameters and experimental conditions are the same as those in Example 1.
[0133] Comparative Example 1
[0134] This comparative example provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that a two-dimensional material is not used, and other parameters and experimental conditions are the same as those of Example 1.
[0135] Comparative Example 2
[0136] This comparative example provides a method for preparing a gold ion layered adsorbent, which is different from Example 1 in that it is not mixed in an emulsion, and other parameters and test conditions are the same as those in Example 1.
[0137] The gold ion layered adsorbents in the above embodiments and comparative examples were subjected to a gold ion adsorption test, the method comprising: leaching a gold-containing material to obtain a gold-containing leaching solution, wherein the gold ions were in the form of [AuCl4] - 、Au(CN) 2- or Au(S2O3)2 3- The leaching solution exists in the form of 1-11. The pH value of the leaching solution is adjusted to 1-11, and the leaching solution is passed through an adsorption column filled with 10 g / L of a gold ion layered adsorbent to adsorb and recover the gold ions. The gold ion adsorption rate data is obtained, and the calculation method is:
[0138] Gold ion adsorption rate (%) = [(initial gold ion concentration - gold ion concentration after adsorption) ÷ initial gold ion concentration] × 100; the calculation results are shown in Table 1 below.
[0139] Table 1 Adsorption rate results of gold ions by gold ion layered adsorbents in Examples and Comparative Examples
[0140]
[0141]
[0142] In summary, the present invention utilizes amino and hydroxyl groups on organic substances as active sites, and composites them with two-dimensional layered materials through electrostatic effects and chemical cross-linking effects to form a complex layered porous structure, thereby improving the mechanical strength and specific surface area of the material, thereby achieving efficient and selective adsorption of gold ions. The preparation method is simple, the conditions are mild, the obtained material has a large adsorption capacity and high selectivity, and can be used to recover gold ions in complex component solutions.
[0143] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0144] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a gold ion layered adsorbent, characterized in that: The preparation method comprises: (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution; (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution; (3) mixing the pretreatment solution described in step (1) and the basic solution described in step (2), stirring and adding a cross-linking agent into the emulsion to obtain a reaction material; (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain the gold ion layered adsorbent; There is no particular order in which steps (1) and (2) are performed.
2. The preparation method according to claim 1, characterized in that: In step (1), the treating agent includes tetramethylammonium hydroxide or CTAB solution; Preferably, the amount of the treatment agent is 10 mL to 100 mL; Preferably, the ratio of the added amount of the treatment agent to the added amount of the two-dimensional material is 1 mL: 1 g to 10 g.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the two-dimensional material includes any one of Ti3C2Tx, Ti2C, Nb2C or V2C, and is more preferably Ti3C2Tx.
4. The preparation method according to any one of claims 1 to 3, characterized in that The pretreatment time is 12h to 48h; Preferably, the pretreatment temperature is 25°C to 80°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), the organic substance includes any one of chitosan, chitosan-modified materials or cyclodextrin-based polymers, and is more preferably a chitosan-modified material; Preferably, the amount of the organic substance added is 0.1 g to 10 g; Preferably, the mass concentration of the acetic acid solution is 1% to 15%; Preferably, in step (2), the stirring time is 3 h to 12 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (3), the volume ratio of the pretreatment solution to the base solution is 1:(0.2-5); Preferably, the emulsion comprises a mixture of liquid paraffin and Span-80; Preferably, the amount of the emulsion is 50 mL to 300 mL.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the stirring speed is 200 r / min to 800 r / min; Preferably, in step (3), the stirring temperature is 20°C to 90°C; Preferably, in step (3), the stirring time is 2 h to 12 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (3), the cross-linking agent includes any one of diisocyanate, acylated polyethylene glycol, adipic acid chloride, citric acid, ethylene glycol glycidyl ether, glutaraldehyde, polyacrylic acid, tetrafluoroterephthalonitrile, sebacic acid chloride or succinic anhydride, or a combination of at least two thereof, and is more preferably any one of diisocyanate, acylated polyethylene glycol or glutaraldehyde; Preferably, the ratio of the amount of the organic substance to the amount of the added cross-linking agent is 1:(1-10).
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (4), the washing treatment temperature is 25°C to 40°C; Preferably, the washing treatment time is 30min to 60min; Preferably, the drying process is vacuum drying; Preferably, the drying temperature is 50°C to 80°C; Preferably, the drying time is 6 hours to 12 hours.
10. The preparation method according to claim 1, characterized in that: The preparation method specifically comprises: (1) adding a two-dimensional material to a treatment agent for pretreatment to obtain a pretreatment solution; (2) dissolving the organic substance in the acetic acid solution and stirring to obtain a base solution; (3) mixing the pretreatment solution described in step (1) and the basic solution described in step (2), stirring and adding a cross-linking agent into the emulsion to obtain a reaction material; (4) subjecting the reaction material of step (3) to solid-liquid separation, washing treatment and drying treatment in sequence to obtain the gold ion layered adsorbent; Step (1) and step (2) are performed in no particular order; in: In step (1), the treatment agent includes tetramethylammonium hydroxide or CTAB solution, the amount of the treatment agent is 10mL to 100mL, the ratio of the amount of the treatment agent added to the amount of the two-dimensional material added is 1mL:1g to 10g, the two-dimensional material includes any one of Ti3C2Tx, Ti2C, Nb2C or V2C, the pretreatment time is 12h to 48h, and the pretreatment temperature is 25°C to 80°C; In step (2), the organic substance includes any one of chitosan, chitosan modified material or cyclodextrin polymer, the amount of the organic substance added is 0.1g to 10g, the mass concentration of the acetic acid solution is 1% to 15%, and the stirring time is 3h to 12h; In step (3), the volume ratio of the pretreatment solution to the base solution is 1:(0.2-5), the emulsion comprises a mixture of liquid paraffin and Span-80, the amount of the emulsion is 50 mL-300 mL, the stirring speed is 200 r / min-800 r / min, the stirring temperature is 20° C.-90° C., the stirring time is 2 h-12 h, the cross-linking agent comprises any one of diisocyanate, acylated polyethylene glycol, adipic acid chloride, citric acid, ethylene glycol glycidyl ether, glutaraldehyde, polyacrylic acid, tetrafluoroterephthalonitrile, sebum dichloride or succinic anhydride, and the ratio of the amount of the organic substance to the amount of the cross-linking agent added is 1:(1-10); In step (4), the washing treatment temperature is 25°C to 40°C, the washing treatment time is 30min to 60min, the drying treatment is vacuum drying, the drying treatment temperature is 50°C to 80°C, and the drying treatment time is 6h to 12h.